The Judicial interpretation in the 2017 constitutional call and the limits of this Constituent Assembly. (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2020)
With the present work is intended to make a hermeneusis of the constituent convocation held in May 2017, to derive from it what would be the consequences of the interpretation made of articles 347, 348 and 349 of the Constitution of 1999. For this purpose, will be performed a dissertation about the call made and the effects of the absence on this occasion of electoral bases duly approved with clear limits and committed to the assembly organ. In a second moment, It is intended to conduct a study of the judicial doctrine of the constituent acts and its inapplicability for the 2017 Constituent Assembly, by undertaking an analysis of the immediate implications of the doctrine of the "constituent acts" and the establishment of the "first and second period of transience "in the gestation of the 1999 Constitution; in the same way, the decisions dictated in the second period of transitoriness and its impossible projection in the current moments will be administered, ending with a conclusive approximation.
Keywords: constitutional assembly; convocation; constituent acts; constitutional laws; precedent